Femina - filmowa współpraca Piotra Szulkina i Krystyny Kofty - Witczak, Krzysztof (Sensus Historiae, 2021)
The article presents the history of the film Femina (1990) from the perspective of the memories of the script author, Krystyna Kofta, a contemporary Polish writer. The essay also presents the achievements of the film’s director, Piotr Szulkin, and his relationship with the writer. The problem of the script, based on the novel titled Pawilon małych drapieżców [Pavilion of small predators], was also raised.